Simar and Wilson two-stage efficiency analysis for Stata - Oleg Badunenko; Harald Tauchmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2018)
When analyzing what determines the efficiency of production, regressing efficiency scores estimated by DEA on explanatory variables has much intuitive appeal. Simar and Wilson (2007) show that this naïve two-stage estimation procedure suffers from severe flaws, that render its results, and in particular statistical inference based on them, questionable. At the same time they propose a statistically grounded bootstrap based two-stage estimator that eliminates the above mentioned weaknesses of its naïve predecessors and comes in two variants. This article introduces the new Stata command simarwilson that implements either variant of the suggested estimator in Stata. The command allows for various options, and extends the original procedure in some respects. For instance, it allows for analyzing both, output- and input-oriented efficiency. To demonstrate the capabilities of the new command simarwilson we use data from the Penn World Tables and the Global Competitiveness Report by the World Economic Forum to perform a cross-country empirical study about the importance of quality of governance of a country for its efficiency of output production.
Keywords: 330; DEA; two-stage estimation; truncated regression; bootstrap; efficiency; bias correction; environmental variables